Ethical issues in rural health care - Klugman, Craig M., 1969-; Dalinis, Pamela M., 1951- (Baltimore : Johns Hopkins University Press, 2008)
'This volume initiates a much-needed conversation about the ethical and policy concerns facing health care providers in the rural United States. Although 21 percent of the population lives in rural areas, only 11 percent of physicians practice there. What challenges do health care workers face in remote locations? What are the differences between rural and urban health care practices? What particular ethical issues arise in treating residents of small communities? Craig M. Klugman and Pamela M. Dalinis gather philosophers, lawyers, physicians, nurses, and researchers to discuss these and other questions, offering a multidisciplinary overview of rural health care in the United States.''This volume is a useful resource for bioethicists, members of rural bioethics committees and networks, policy makers, teachers of health care providers, and rural practitioners themselves.'--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Rural health services -- Moral and ethical aspects -- United States